Bidirectional DC-DC Converter with High Voltage Gain for the Charge/Discharge Control of Storage Systems - Pires, Vítor Fernão (2016)
This paper presents a study of a bidirectional dc-dc converter with high voltage gain to regulate the charge and discharge of electrochemical storage systems. The converter is characterized by quadratic voltage gain characteristics in both directions. In this context it can be used to regulate a dc interface between the storage system and a dc/ac converter connected to the electrical grid. It will be analysed the converter in ideal and non-ideal conditions. A control system to regulate the output voltages and currents are also proposed. Simulation results are presented in order to validate the control system associated to the converter for the charge/discharge of the storage system.